Profit of Traditional Food Stall Traders in Facing Modern Restaurants in the Perspective of Service - Mujayanah Mujayanah; Rahmat Agus Santoso (Indonesian Vocational Research Journal, 2022)
Traditional food stall traders in Cerme District experienced a decrease in profit due to the existence of Modern Restaurant. Traditional food stall traders still survive in the face of competition problems with modern restaurants. This study aims to determine the profit of traditional food stalls facing modern restaurants in the perspective of service quality. By collecting data from 5 informants and 1 key informant as the initial opening of the research to find more accurate results. The presentation of the data was carried out using the interactive model of Miles and Huberman (1984), namely data collection, data reduction, data display and verification. The results of the data analysis of the traditional food stall traders survive in the face of modern restaurants and still earn profits by implementing service quality through the perspective of tangible, reliability, responsiveness, assurance and empathy. The results of the research on the profits of traditional food stall traders in dealing with modern restaurants in a service perspective are Tangible: Cleanliness and tidiness of traditional food stalls, Reliability: Speed ​​and accuracy, Responsiveness: Facilities and inventory of goods, Assurance: Maintaining ethics, polite and patient language, Empathy: Buyer's request. Keywords: Profit; Traditional Food Stalls; Modern Restaurant; Service Quality Perspective